The Effect of Timing of Mandibular Distraction Osteogenesis on Weight Velocity in Infants Affected by Severe Robin Sequence - Zhe Mao; Ricardo Battaglino; Jiawei Zhou; Yingqiu Cui; Mayank Shrivastava; Gabriel Tian; Faezeh Sahebdel; Liang Ye (MDPI AG, 2022)
Background: Impaired weight gain is prevalent in Robin Sequence (RS) newborns. Although mandibular distraction osteogenesis (MDO) has been proven to improve oral feeding, its impact on postoperative weight gain remains unclear. The purpose of this study is to explore whether MDO can help RS babies reach a normal weight, as well as the effect of MDO timing on weight velocity. Methods: One hundred infants with severe RS and one hundred with normal controls met the inclusion criteria for the study. Included patients underwent MDO. Weights at different timing points were recorded and analyzed and compared to normal controls. Results: After the distractor removal weights of patients undergoing MDO at <1 month and 1-2 months were close to the normal control (6.81 ± 0.93 kg versus 7.18 ± 0.61 kg, p = 0.012, and 6.82 ± 0.98 kg versus 7.37 ± 0.75 kg, p = 0.033, respectively), the weights of patients undergoing MDO at 2-3 months and 3-4 months still lagged behind (7.56 ± 1.29 kg versus 8.20 ± 0.61 kg, p = 0.000206 and 7.36 ± 1.05 kg versus 8.25 ± 0.77 kg, p = 0.004, respectively). The weights of all RS infants undergoing MDO showed no significant difference compared to the controls when they aged to 1 year (9.34 ± 0.99 kg versus 9.55 ± 0.45 kg, p = 0.254 for MDO at <1 month; 9.12 ± 0.91 kg versus 9.33 ± 0.46 kg, p = 0.100 for MDO at 1 to 2 months; 9.38 ± 0.29 kg versus 9.83 ± 0.53 kg, p = 0.098 for MDO at 2 to 3 months; and 9.38 ± 0.29 kg versus 9.83 ± 0.53 kg, p = 0.098 for MDO at 3 to 4 months). Conclusion: The MDO procedure helped patients with severe RS to reach a normal weight; and MDO intervention was recommended at an early stage for early weight gain.